THE APPLICATION OF THE ISO 9001:2015 QUALITY MANAGEMENT SYSTEM TO SERVICE PERFORMANCE AND CUSTOMER SATISFACTION AT BPVP BANDUNG BARAT - Hanafi, Imron (Qawwam : The Leader's Writing, 2025)
ISO 9001:2015 Quality Management (SMM) is one of the strategic efforts of public sector organizations in improving service quality and customer satisfaction. This study aims to analyze the implementation of ISO 9001:2015 SMM and its impact on service performance and customer satisfaction levels at the Bandung Barat Vocational and Productivity Training Center (BPVP). The research method used was descriptive qualitative with data collection techniques through documentation studies of quality documents, standard operating procedures (SOPs), internal audit reports, and customer satisfaction survey data. The results show that BPVP West Bandung has consistently implemented the principles of ISO 9001:2015, including customer focus, leadership, employee involvement, process approach, continuous improvement, and fact-based decision making. The implementation of the ISO 9001:2015 QMS has been proven to contribute positively to improving service quality and customer satisfaction, as indicated by an increase in the customer satisfaction index from year to year. This study concludes that the effective implementation of the ISO 9001:2015 QMS can improve organizational performance and the quality of public services.